Foundations of Japanese language - Soga, Matsuo (Taishukan, 1978)
It is composed of thirty lessons intended for one academic year for colleges and universities on the North American continent. It is an introductory text for mature native speakers of English who have no previous knowlege of japanese language. Each lesson is organized with introduction of new vocabulary intems, model sentences of Japanese preceded by thier English equivalent, explanations of the grammatical points of the lesson, exercises, oral practice, and conversations.